[OP.3C.01] COMPARISON BETWEEN EUROPEAN SYSTEMATIC CORONARY RISK EVALUATION AND ITALIAN CUORE ALGORITHMS IN ADULT OUTPATIENTS FOLLOWED BY GENERAL PRACTITIONERS AND SPECIALISED CENTRES. (September 2017) - Tocci, G.; Gallo, G.; Costanzi, V.; Attalla, N.; Simonelli, F.; Presta, V.; Figliuzzi, I.; Citoni, B.; Battistoni, A.; Ferrucci, A.; Volpe, M.
Abstract : Objective: Global cardiovascular (CV) risk stratification based on either European Systematic Coronary Risk Evaluation (SCORE) or Italian CUORE algorithms should be performed in all adult outpatients by both general practitioners (GPs) and specialised physicians (SPs). Design and method: To compare individual CV risk profile by using either European SCORE and Italian CUORE algorithms in adult outpatients followed by GPs and SPs in Italy. All available data were centrally analysed for global CV risk assessment and rates of control of major CV risk factors, including blood pressure (BP), serum cholesterol, triglycerides and glucose levels. CV risk profile characterization was based on both SCORE and CUORE algorithms. Study population was stratified according to referring physicians (GPs, cardiologists, diabetologists, other SPs). Results: We analysed data from an overall population sample of 10, 404 adult outpatients (age 60.76.5 years, BMI 28.34.9 kg/m 2, BP 136.714.4/82.18.2 mmHg, total cholesterol 212.240.7 mg/dl, HDL cholesterol 50.812.3 mg/dl), among whom 7, 767 (74.7%) were followed by GPs, 1, 239 (11.9%) by cardiologists, 1, 006 (9.7%) by diabetologists and 392 (3.8%) by other SPs. Systolic/diastolic BP, total/LDL cholesterol and triglycerides levels were higher and HDL cholesterol was lower in patients followed by GPs and cardiologists compared to other groups. Conversely, BMI and fasting glucose levels were higher in patients followed by diabetologists than in other groups. All major CV risk factors and comorbidities were more frequently reported and controlled in patients followed by cardiologists than in the other groups, with the only exception of diabetes. Both European SCORE (4.74.5) and Italian CUORE (13.711.5) were significantly higher in outpatients followed by cardiologists than in those followed by GPs (4.03.6 and 11.59.7) and diabetologists (3.73.5 and 10.39.2) or other SPs (3.32.8 and 9.47.4; P < 0.001 for all comparisons). Conclusions: Despite proper use of drugs and better pharmacological control of major risk factors, both European SCORE and Italian CUORE algorithms reported higher CV risk profile in patients followed by cardiologists than in patients followed by diabetologists, GPs, and other SPs.